2021
DOI: 10.1177/15459683211034758
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Head Motion is a Greater Motor Control Challenge than Transient Head Motion in Patients with Loss of Vestibular Function

Abstract: Background. The vestibular system is vital for gaze stability via the vestibulo-ocular reflex, which generates compensatory eye motion in the direction opposite to head motion. Consequently, individuals with peripheral vestibular loss demonstrate impaired gaze stability that reduces functional capacity and quality of life. To facilitate patients’ compensatory strategies, two classes of gaze stabilization exercises are often prescribed: (i) transient (eg, ballistic) and (ii) continuous. However, the relative be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Finally, here we have further shown that head kinematics and step cycle duration—both during short duration FGA and extended duration gait rehabilitation exercises—are predictive of several clinical measures, but not of subjective quality of life assessments. In this context, our findings add to a growing body of work demonstrating comparable conclusions based on head movements during other classes of vestibular exercises (i.e., gaze 55 , 56 and balance 49 ). Moreover, we found that kinematic measures from both short and extended duration conditions better predicted physiological (i.e., vHIT) measures preoperatively than postoperatively.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, here we have further shown that head kinematics and step cycle duration—both during short duration FGA and extended duration gait rehabilitation exercises—are predictive of several clinical measures, but not of subjective quality of life assessments. In this context, our findings add to a growing body of work demonstrating comparable conclusions based on head movements during other classes of vestibular exercises (i.e., gaze 55 , 56 and balance 49 ). Moreover, we found that kinematic measures from both short and extended duration conditions better predicted physiological (i.e., vHIT) measures preoperatively than postoperatively.…”
Section: Discussionsupporting
confidence: 80%
“…Comparisons were also made between the head movement kinematics of preoperative versus postoperative VS subjects. Additionally, we correlated these kinematic data with standard clinical outcome measures [16][17][18][19] to determine whether postoperative head kinematics during balance exercises correlate with preoperative clinical measures. Finally, we addressed whether it was possible to compute a robust "kinematic score" based on head kinematic data obtained from a subset of exercises.…”
Section: Introductionmentioning
confidence: 99%
“…The vestibular system is highly adaptable [12] with compensation for eighth cranial nerve section typically occurring within seven days [27]. Furthermore, individuals may learn how to cope with their symptoms by deploying strategies that allow them to remain functional despite their vestibular impairment [49]. This behavior, largely based on the apparent improvement of symptoms, is explicitly seen with vestibular schwannoma, in which patients demonstrate better postural control at intermediate stages of tumor development, only to observe further balance declines at later stages when the tumor is significantly larger and compensatory strategies are no longer effective [35].…”
Section: Duration To Seek Carementioning
confidence: 99%